Decision Graphs and Their Application to Software Testing. (11th April 2013) - Gold, Robert
Abstract : Control flow graphs are a well-known graphical representation of programs that capture the control flow but abstract from program details. In this paper, we derive decision graphs that reduce control flow graphs but preserve the branching structure of programs. As an application to software engineering, we use decision graphs to compare and clarify different definitions of branch covering in software testing.